7-HIDROKSI-6-METOKSI KUMARIN (SKOPOLETIN) DARI KULIT BATANG Chisocheton celebicus (MELIACEAE) - Dewa G. Katja; Andre A. Sonda; Desi Harneti P. Huspa; Tri Mayanti; Unang Supratman (Jurnal Kimia (Journal of Chemistry), 2015)
7-hydroxy-6-methoxy coumarin (scopoletin) has been isolated from the bark of Chisocheton celebicus (Meliacee) using several chromatographic techniques.  The chemical structure of 7-hydroxy-6-methoxy coumarin was identified on the basis of spectroscopic data including UV, IR, 1D-NMR, 2D-NMR and mass along with by comparison with those spectral data previously reported. The discovery of scopoletin from the bark C. celebicus reported for the first time in this study.